Profile of food allergens in urticaria patients in Hyderabad - Hari Sai Priya; Anuradha B; Vijayalakshmi V; Latha Suman; Murthy KJR (Indian Journal of Dermatology, 2006)
Urticaria is one of the manifestations of a pattern of allergy. The associated disorders are vascular reaction and wheals. The objective of this study was to determine the prevalence of sensitivity to food allergens in Hyderabad in patients suffering from allergy. Four hundred and one patients attending the Allergy Clinic at BMMRC, with a confirmed diagnosis of bronchial asthma, rhinitis or urticaria were skin tested. Total sIgE levels were estimated by ELISA. Positivity to beans (53%) was highest, followed by mustard (41%) and cardamom (40%). Often patients having positive skin tests to food allergens which may have skin reactions to foods prove to be a problem. Foods that produce significant positive skin tests could be avoided in the diet; however, other foods that do not show skin reactions may contribute to the disease.